2020
DOI: 10.4102/sajce.v10i1.800
|View full text |Cite
|
Sign up to set email alerts
|

A mathematics teacher’s response to a dilemma: ‘I’m supposed to teach them in English but they don’t understand’

Abstract: A mathematics teacher's response to a dilemma: 'I'm supposed to teach them in English but they don't understand'',

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…They concluded that restricting students to the use of English during verbal discourse in the classroom limits the students' ability to demonstrate their mathematical thinking. Several other South African studies have had similar findings (Webb, Nemer, & Ing, 2006;Setati, Chitera, & Essien, 2009;Phakeng, 2018;Robertson & Graven, 2020).…”
Section: The Development Of Mathematical Thinking Through Discoursesupporting
confidence: 67%
See 1 more Smart Citation
“…They concluded that restricting students to the use of English during verbal discourse in the classroom limits the students' ability to demonstrate their mathematical thinking. Several other South African studies have had similar findings (Webb, Nemer, & Ing, 2006;Setati, Chitera, & Essien, 2009;Phakeng, 2018;Robertson & Graven, 2020).…”
Section: The Development Of Mathematical Thinking Through Discoursesupporting
confidence: 67%
“…Qhaw identified the language used in the question as increasing the level of difficult of the question for him: From his response, it can be inferred that the language used in the mathematics problem had an impact on his comprehension of the question. Several studies (Chitera, Kasoka, & Thomo, 2016;Robertson & Graven, 2020;Robertson & Graven, 2020a) have established that mathematics students who are second language English speakers experience difficulties when engaging with mathematics word problems where language proficiency is vital. The language barrier was not expected to be a problem for these participants since they were third year students, however Qhaw indicated that his difficult solving the second problem was related to language, in part.…”
Section: Create Mental Images Without Even Drawing Them Down On Paper...mentioning
confidence: 99%
“…The response of PMT4 indicates that language proficiency can have an impact on the understanding of mathematics problems. Studies (Chitera et al, 2016;Robertson & Graven, 2020a, 2020b have affirmed that second-language English-speaking mathematics students may struggle with word problems, where language proficiency is critical. Although English is the medium of instruction at the institution, where the participants were studying, PMT4's difficulty understanding the problem indicates that language barriers can still be a challenge for third-year mathematics students.…”
Section: Visual Mediatorsmentioning
confidence: 99%
“…Penggunaan bahasa Inggeris yang meluas di beberapa buah negara, telah membawa kepada perubahan dasar pendidikan Matematik. Terdapat peningkatan dalam bilangan pelajar di seluruh dunia yang mempelajari matematik dalam bahasa yang bukan bahasa pertama mereka (Robertson & Graven, 2020a).…”
Section: Sorotan Literaturunclassified
“…TITLE-ABS-KEY( ("strategy*" OR "practice*" OR "approach*" OR "method*" OR "process*") AND ("mathematics") AND ("English medium" OR "addition language" OR "second language" OR "English language learner*" OR "Second Language Learner*" OR "bilingual" OR "foreign language*" OR "dual-language " OR "multilingual") ) Web of Science TS = (( "strategy*" OR "practice*" OR "approach*" OR "method*") AND ( "mathematics*" ) AND ("English medium" OR "addition language" OR "second language" OR "English language learner*" OR "Second Language Learner*" OR "bilingual" OR "foreign language*" OR "dual-language " OR "multilingual")) Robertson & Graven, 2020a;Sipholi & Machaba, 2021;Tai & Wei, 2021a, 2021b, 2021c. Terdapat lima kajian menggunakan kaedah kuantitatif (DeVries et al, 2020;le Pichon et al, 2021;Makonye, 2019;Ní Ríordáin, 2018;Outhwaite et al, 2020) manakala hanya sebuah kajian yang menggunakan kaedah gabungan (Luevano & Collins, 2020).…”
Section: Pangkalan Data Kata Kunci Yang Digunakan Scopusmentioning
confidence: 99%